2019
DOI: 10.3166/phyto-2019-0195
|View full text |Cite
|
Sign up to set email alerts
|

Composition chimique, activités anti-inflammatoire, antalgique et cytotoxique in vivo de l’extrait méthanolique des feuilles d’Olea europaea

Abstract: Olea europaea est une plante médicinale largement utilisée en médecine traditionnelle en Algérie. Dans la présente étude, les activités anti-inflammatoire, antalgique et cytotoxique de l’extrait méthanolique des feuilles d’Olea auropaea sont évaluées. De même, une étude chromatographique analytique a été réalisée pour identifier les différentes familles de composés chimiques contenus dans cet extrait. Les résultats obtenus montrent que l’analyse qualitative de l’extrait méthanolique des feuilles d’olivier par … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Elsewhere the extracts of F. virosa tested on this pain significantly reduced its symptoms. Authors have reported that the reduction in pain induced by acetic acid in mice may be due to the presence of polyphenols such as flavonoids [39]. Thus present extracts, all rich in polyphenols with antioxidant, anti-inflammatory and analgesic properties, could act on the functional component of the prostate by reducing its volume and the pressure exerted by its muscles on the urethra.…”
Section: Discussionmentioning
confidence: 97%
“…Elsewhere the extracts of F. virosa tested on this pain significantly reduced its symptoms. Authors have reported that the reduction in pain induced by acetic acid in mice may be due to the presence of polyphenols such as flavonoids [39]. Thus present extracts, all rich in polyphenols with antioxidant, anti-inflammatory and analgesic properties, could act on the functional component of the prostate by reducing its volume and the pressure exerted by its muscles on the urethra.…”
Section: Discussionmentioning
confidence: 97%
“…Oleuropein is a seco-iridoid, a fairly bitter compound that breaks dawn fairly quickly, therefore it seems preferable to use standardized extracts from the olive leaf (Glycerin maceration, stabilized extract) rather than a decoction or aqueous infusion. Olive leaf is also anti-diabetic and clinical studies confirm its indication to prevent atherosclerosis (Lakache et al, 2019, Lamzira et al, 2014, Susalit et al, 2011.…”
Section: Introductionmentioning
confidence: 99%